HUBUNGAN KOORDINASI MATA TANGAN DAN DAYA LEDAK OTOT TUNGKAI DENGAN KETEPATAN SMASH PADA KEGIATAN EKSTRAKURIKULER BOLA VOLI SMA NEGERI 1 SENTAJO RAYA - Yudy Maryadi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: based on the researcher observations in field during the training activities carried out by students who took exstracurricular activities at SMAN 1 Sentajo Raya defeat is caused by a lack o the ability to smash, especially one in front of the net, either in any rehearsal or incompetition like the ball gets in the net, the ball gets out o the field, the ball gets knocked out on the target. The purpose o the study is to know significant relationship between the limb muscles exprosive and aye-hand coordination together against to the ability to smash. The population in this study are all students who follow volley ball extracuricullar at SMAN 1 Sentajo Raya. There were 20 male students, the sampling technique in this research or total sampling technique with his research sample. there are 20 athletes, the instrument in this research are throw and cactch the ball, vertical jump, and the precision o the smash. Results obtained in analysis using a simple and double correlation based on the results o the research can beadvanded as follows: statistical analysis war obtained r count = 0,537, and r table to a dagree a = 0,05 next 0,444 thus r count > r table. It means there is significant connection between the coordination at the Eye-Hand and the precision of a smash. Statistical analysis was obtained r count = 0,831 and r table to a degree a = 0,05 next =0.444 thus r count > r table. It means there is significant connection between the muscle charges, the legs with aprecision smash. Statistical analysis obtained r count = 0,875 and r table to a degree a 0,05 next 0,444 thus, r count > r = table, it meansthere is significant connection between, the muscular explosive lines, limbs and coordination to the abillity of the smash.Key Words: Muscle Explosive Power Eye-Hand Coordination, Smash Accuracy